Beckmann (Modern art and modernism : Manet to Pollock, 1983)
Critical analysis of the work of the 20th century German expressionist artist Max Beckmann, The social and political criticism in Beckmann's art is discussed in the context of Hitler's attempt to control German culture in the 1930's